Compressional characteristics and tableting properties of starches obtained from four dioscorea species (2009)
The compressional characteristics and tableting properties of starches from four yam species namely Dioscorea dumetorum Pax (Bitter); Dioscorea oppositifolia L (Chinese); Dioscorea alata L.DIAL2 (Water) and Dioscorea rotundata Poir (White) were Investigated in comparison with corn starch. The physicochemical properties of the starches were evaluated using established methods while the compressional characteristics were analyzed using density measurements, and the Heckel and Kawakita equations. The properties of the tablets were assessed using Tensile strength (T), Brittle Fracture Index (BFI), Friability (F) and Disintegration Time (DT). The physicochemical properties of the starches varied considerably among the various species. The ranking for the mean yield pressure (Py) obtained from Heckel plots was Chinese > Bitter>Corn > White>Water while the ranking was the reverse for another pressure term, Pk, obtained from Kawakita plots. The ranking for T was Chinese > Bitter>Corn > White>Water. The T values were inversely related to Pk values. The ranking of DT was Bitter>Chinese>Corn>White> Water, while the ranking was reverse for BFI and F. Water and White yam starch tablets did not conform to the Pharmacopoeia requirements on friability (≤1%) while all the starch tablets except Bitter yam starch conformed to the requirements on disintegration (≤15minutes). Thus, the starches could be useful as excipients in tablet formulations.